1985
DOI: 10.1111/j.1600-051x.1985.tb00936.x
|View full text |Cite
|
Sign up to set email alerts
|

Gram negative species associated with active destructive periodontal lesions

Abstract: Apical subgingival plaque samples were taken from 19 subjects exhibiting active destructive periodontal disease. The predominant cultivable Gram negative species from 50 active sites were compared to 69 inactive sites of comparable pocket depth and attachment level loss. Active disease sites were chosen which showed a significant loss of attachment within a two-month interval. Proportions of Gram negative rods were higher in active periodontal disease sites than in inactive sites. Species which were found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
263
0
4

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 442 publications
(279 citation statements)
references
References 38 publications
12
263
0
4
Order By: Relevance
“…nucleatum is of considerable interest to oral microbiologists. It is the most frequently detected species in predominant cultivable studies of the microbiota of subgingival plaque, averaging 8 to 10% of the microbiota (5, 6,20). F. nucleaturn has been associated with lesions of destructive periodontal disease, but has also been found in high numbers in successfully treated sites and in healthy sites (5, 6,20).…”
mentioning
confidence: 99%
“…nucleatum is of considerable interest to oral microbiologists. It is the most frequently detected species in predominant cultivable studies of the microbiota of subgingival plaque, averaging 8 to 10% of the microbiota (5, 6,20). F. nucleaturn has been associated with lesions of destructive periodontal disease, but has also been found in high numbers in successfully treated sites and in healthy sites (5, 6,20).…”
mentioning
confidence: 99%
“…Ebersole et al (22) reported that E. corrodens was associated with sites in periodontal pockets, whereas another study (23) demonstrated a weak association with chronic periodontitis, and a third study (24) showed that there was no significant difference between active and inactive sites in the distribution of E. corrodens. In 2002, Avila-Campos and Velasques-Mendez (25) evaluated the prevalence of putative periodontopathogens in periodontal patients and healthy subjects and found that E. corrodens and F. nucleatum were not significantly associated with periodontal disease.…”
Section: Discussionmentioning
confidence: 95%
“…Campylobacter rectus is a poorly described Gram-negative, oral bacterium that has been implicated as a cause of periodontitis [3][4][5]. Recent studies indicate that women with periodontitis are seven times more likely to experience preterm labor than their healthy counterparts [6,7].…”
Section: Introductionmentioning
confidence: 99%